30‐3: Distinguished Paper: Sub‐Micron Full‐Color LED Pixels for Micro‐Displays and Micro‐LED Main Displays. Issue 1 (25th September 2020) - Ra, Yong-Ho; Wang, Renjie; Stevenson, Matthew; Coe-Sullivan, Seth; Mi, Zetian
Abstract : We demonstrate a bottom‐up approach to the construction of micro‐LEDs as small as 150nm in lateral dimension. Molecular Beam Epitaxy (MBE) is used to fabricate such nanostructured LEDs from InGaN, from the blue to red regions of the spectrum, providing a single material set useful for an entire RGB display.